Cooling system based on double-ball motor control valve. (May 2021) - Mu, Hongyu; Wang, Yinyan; Teng, Hong; Jin, Yan; Zhao, Xingtian; Zhang, Xiaolong
To realize eco-models based on (where 3R represents reducing, reusing, and recycling), both researchers and automobile development departments use controllable components to reduce vehicle fuel consumption and emissions. In this context, this paper presents the design of a double-ball motor control valve (DB-MCV). When compared with use of a traditional thermostat, use of the proposed valve in a Worldwide Harmonized Light Vehicles Test Cycle (WLTC) allows the coolant temperature to be controlled accurately as per the vehicle operating conditions, with control accuracy of ±1°C. Using this approach, the engine pre-heating time is reduced by 61 s, the total hydrocarbon (THC)) emission is reduced by 6.79%, the CO emission is reduced by 7.18%, and NOX emission is reduced by 4.84%. Under the same vehicle and working conditions, the engine fuel consumption is reduced by 2.31% on average. Under the cabin heating condition, the cabin temperature can be increased by 4.3°C, which improves the thermal comfort of the driver. When the vehicle is stopped after running at high speed and the engine is idling, the coolant temperature in the engine decreases rapidly, which reduces the risk of a hot dip occurring in the engine.